Need to ban tobacco consumption in public places to protect non-smokers health - Accinelli Tanaka, Roberto Alfonso (2012)
We describe in this paper the damage caused by tobacco smoke not only to smokers, but also to persons exposed to second-hand tobacco smoke, and also the impact of this addiction in the economy. A review of the most important papers is presented, emphasizing the time when these studies were performed, which finally led many governments to issue laws aiming to limit the health damage caused by tobacco smoke. We also review laws for having tobacco-free environments, and the effects achieved with their implementation, including the economical consequences.